FAKTOR-FAKTOR KESULITAN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN CAD PENGGUNAAN AUTOCAD PADA SISWA JURUSAN TEKNIK GAMBAR MESIN SMKN 2 KOTA SERANG - Mochamad Dafa Faizal; Iman, Atep; Supriyatna, Deddy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the factors influencing learning outcomes in the CAD subject using AutoCAD software among twelfth-grade students of the Mechanical Drawing Engineering Department at SMKN 2 Serang City. The research employs a descriptive quantitative method with a saturated sampling technique, involving 37 students as both the population and the sample. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability and were analyzed using descriptive statistics. The results indicate that students’ internal factors are in the moderate category, reflected in suboptimal motivation, interest, attention, and learning readiness, while external factors also fall within the moderate to high category, with remaining constraints in learning facilities and teaching methods that do not fully support effective AutoCAD practice. Furthermore, students’ learning outcomes in cognitive, psychomotor, and affective domains are categorized as moderate. These findings suggest that although students possess a basic understanding, their ability to independently apply AutoCAD still requires improvement through the enhancement of both internal and external learning.